Influence of prehospital management on the outcome of spinal cord decompression sickness in scuba divers. Issue 10 (7th February 2022) - Andre, Sophie; Lehot, Henri; Morin, Jean; Louge, Pierre; de Maistre, Sébastien; Roffi, Romain; Druelle, Arnaud; Gempp, Emmanuel; Vallée, Nicolas; Vergne, Muriel; Blatteau, Jean-Eric
Abstract : Background: Decompression sickness (DCS) with spinal cord involvement has an unfortunately high rate of long-term sequelae. The objective of this study was to determine the association of prehospital variables on the outcome of spinal cord DCS, especially the influence of the initial clinical presentation and the time to recompression. Methods: This was a retrospective study using prospectively collected data which included divers with spinal cord DCS seen at a single hyperbaric centre study from 2010 to 2018. Information regarding dive, latency of onset of symptoms, time to recompression and prehospital management, that is, use of oxygen, treatment and means of evacuation, were analysed as predictor variables. The initial clinical severity was estimated by the score of the French society of diving and hyperbaric medicine (MEDSUBHYP). The primary end point was the presence or absence of sequelae at discharge assessed by the modified score of the Japanese Orthopedic Association. Results: 195 divers (48±12 years, 42 women) were included. 34% had neurological sequelae at discharge. In multivariate analysis, a MEDSUBHYP score ≥6 and a time to recompression >194 min were significantly associated with incomplete neurological recovery (OR 9.5 (95% CI 4.6 to 19.8), p<0.0001 and OR 2.1 (95% CI 1.03 to 4.5), p=0.04, respectively). Time to recompression only appeared to be significant for patients with high initial clinical severity. As time to recompression increased, the level of sequelae also increased (p=0.014). Conclusion: Determining the initial clinical severity is critical in identifying patients who need to be evacuated for recompression as quickly as possible.